ASSESSMENT OF EMOTIONAL INTELLIGENCE AMONG STAFF NURSES OF TERTIARY CARE HOSPITALS OF KARACHI, PAKISTAN - Shahida Khan; Tharo Khan; Muhammad Ibrahim Ansari et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: To assess the emotional intelligence of registered nurses of public and private tertiary care hospitals. DESIGN: Cross sectional study of six months (Jan 2016 to June 2016). SETTING: Study conducted in 3 public and private hospitals of capital of Sindh SUBJECTS: Sample of 368 registered staﬀ nurses. INTERVENTION: Close ended 5 ranking Likert Schutte self reporting emotional intelligence scale was used with convenient sampling technique. MAIN OUTCOME MEASURES: To assess emotional intelligence. RESULTS: 145 males and 223 females were respondents. Among them 232(63%) were RN/RM, 128(34.8%) were B.Sc N (Nursing graduate) and 8(2.2%) were having M.Sc. N degree. Majority of nurses were having 2-6 years of experience as 167(45.4%) and the least are 8(2.2%) who were having 31-35 years of experience. In Likert Schutte scale almost the maximum score of the respondents responded “Agree” numbered as 7620 and the least are 193 as “strongly disagree” of the item contents. Only p-value of gender-emotional intelligence variables was found signiﬁcant p≤ 0.005. CONCLUSION: Staﬀ nurses working at tertiary care hospitals showed utilization of high level of emotional intelligence in their daily routine